An assessment of the role played by the Child Protection System in protecting children’s rights: a case of Bulawayo urban 2004- 2014 - Mhangwa, Gina (Midlands State University, 2017)
The purpose of the study is to assess the role played by the Child Protection System (CPS) in protecting children’s rights in Bulawayo urban. The research will explore the impact of the CPS in protecting children’s rights in the area of study. The research will pay particular attention to children’s right to name and nationality, education, health, protection from child labour and protection from abuse and exploitation. This is mainly because these are the issues that need more attention in the area of study. In Zimbabwe, the CPS has become an integral component in improving children’s welfare and development. Cases of child rights violation are being recorded almost on a daily basis in Bulawayo urban, for example, school dropouts are still high, poor health care and services, children are victims of child labour, sexual abuse and all forms of violence against children The researcher will also aim to highlight some of the mechanisms that have been put forward to try and protect children’s right. Hence to fully understand on the role played by the CPS in protecting children’s rights a combination of research methodologies will be used and these include qualitative and desk research. Questionnaires and structured face to face interviews will be used to collect data. The study will also outline recommendations on what can be done so as to improve on the protection of children’s rights.